Idades e género na literatura e na arte da Grécia antiga - Luísa de Nazaré Ferreira (Classica Digitalia: Humanitas Supplementum - Estudos Monográficos, 2015)
This volume puts forward several reflections about the idea of age and gender in Ancient Greece. It brings together seven studies by Spanish, Portuguese and Argentinian researchers. The essays gathered here are based upon information from different sources: literary, iconographic, epigraphic, and social. They do not focus on the citizen, i.e. on the adult male as the citizen, according to Aristotle's definition, but on children, elderly, maidens. Even the field of male prostitution is explored. It is a study which, based on the abundant bibliography which has developed over recent years on these issues, offers an overall reflection on the margins of citizenship seen from the parameters of gender and age.